Effect of Acupressure on Severity and Outcome of Uremic Pruritus in Hemodialysis Patients: A Randomized Clinical Trial - Jalali, Eghlima; Rezaie, Somayeh; Goli, Shahrbanoo; Fadaee Aghdam, Nasrin; Khajeh, Mahboobeh (Shahroud Journal of Medical Sciences, 2025)
Introduction: One of the troublesome problems of patients in the end stages of renal disease (ESRD) is uremic pruritus (UP), which can adversely affect the quality of life, treatment process, and longevity of patients. The present study investigated the effect of acupressure on the severity and outcome of UP in hemodialysis patients. Methods: In this study's three-group randomized controlled clinical trial, 105 patients undergoing hemodialysis were selected by convenience sampling. Patients were randomly assigned to acupressure (n=35), sham (n=35), and control (n=35) groups. The acupressure group received acupressure in SP 6, SP 10, ST 36, and L I11 points, while the sham group received acupressure in non-real points. The severity and outcome of UP were evaluated before, 4, and 12 weeks after the intervention using a Visual Analog Scale (VAS) and a 5-D itch scale, respectively. Finally, data collected from 105 participants were analyzed using SPSS version 25 software. Kruskal Wallis and Friedman tests were used to compare the severity and outcome of UP between and within groups, respectively. Result: UP's severity and outcome after the intervention significantly improved in the acupressure group compared to the other two groups (p<0.05). Conclusion: The use of acupressure can improve the severity and outcome of UP in hemodialysis patients and training this method to nurses and patients is recommended as a safe and accessible way to heal their pruritus.